Structural Bases of Postresuscitative Heart Failure - V. T. Dolgikh; A. M. Kochetov; S. V. Dolgikh (Общая реаниматология, 2005)
An experiment on 106 non-inbred male albino rats undergone 4-minute clinical death from acute blood loss has revealed that the first three days after resuscitation are marked by a concomitance of vascular disorders and cardiomyocytic dystrophic changes, the leading role being played by sludge, stasis, thrombosis, increased vascular permeability, perivascular edema, and hemorrhages. Cardiomyocytic destruction (various contractures, block-like myofibrillolysis, myocytoly-sis) is a structural basis of postresuscitative heart failure. Three days later the heart displayed concomitant processes of recovery and damage. Three types of cardiac morphological changes have been identified in relation to the ratio of these processes.